SURGICAL APPROACH TO THE TREATMENT OF PATIENTS WITH PATHOLOGICAL FRACTURES CAUSED BY METASTASIS AND PRIMARY MALIGNANT TUMORS IN LOCOMOTOR SYSTEM - V. L. Skryabin; A. S. Denisov; V. M. Ladeyshikov; S. B. Bulatov (Креативная хирургия и онкология)
Work objective-determination of pathological fracture frequency caused  by malignant tumors in locomotor system, indications and possible treatment study. The analysis of treatment of 44 patients was made. It is shown, that  the frequency of this kind of pathology is 0.4%. 70.5%  of patients were female, 29.5%male. The average age of patients was 53 years. The primary tumor  wasn’t found in 34%  of cases.  The most frequent segment of  metastasis spread was  femoral bone84.4%.  Operative therapy included exsection of the tumor followed by endoprosthesis replacement (15 cases), defect replacement with artificial materials (6), segment shortening (9), fracture stabilization only (11), biopsy (3).  Pathologic  fractures occurred due to breast cancer  metastasis in 16 cases (36,3%). 19 (43,2%) people died in a year after the surgery. 14 (31,8%) during the second year. 15.9% (7 people) lived for thee years and 4 patients (9.1%) lived for more than 5 years after the surgery. All operated  patients were   socially  adapted, fully  self-maintaining,  had   no  pain syndrome caused  by operated extremity.Due to this experience of pathologic fractures treatment we recommend active surgical approach. The surgery doesn’t affect the disease outcome, but makes patients more socially adopted for a considerable period of time.